Implementasi Aplikasi Linktree SiLaPasTar untuk Akses Informasi dan Pengurangan Stigma Warga Binaan Lapas Kelas IIB Blitar - Ramadan, Novan Rizky; Riupassa, Goerge Rudolf Jacob A.; Sopacua, Hendro Micha Yabes; Aulia, Qisthina; Butar-Butar, Herry F.; Muhammad, Ali (Fanshur Institute, 2025)
The implementation of the Linktree Application for the Blitar Prison Service System (SiLaPasTar) represents a digital innovation designed to enhance information access and services for visitors and inmates at Class IIB Blitar Prison. This application aims to simplify administrative processes, such as visitor service registration, inmate integration rights application (PB, CB, CMK), and provide other essential information related to the prison. The methodology used in this research includes needs analysis, system design, implementation, and evaluation. The results of the research indicate that the SiLaPasTar application successfully increased efficiency and transparency in prison administrative services and reduced negative stigma towards inmates